Mesenteric cystic lymphangioma mimicking an ileo-colic intussusception - Elisa Mina; Giulia Fusi; Rossella Angotti; Niccolò Nardi; Mohamed Vincenti; Mario Messina; Francesco Molinaro; Mirko Bertozzi (Elsevier, 2020)
Lymphangioma accounts for 5% of benign pediatric tumors and less than 1% is located in the abdomen. Indeed mesenteric cystic lymphangioma is a rare benign abdominal mass and its pathogenesis is still unknown.Mesenteric cystic lymphangioma is often diagnosed incidentally. Nevertheless, in some cases its clinical presentation can mimic several common surgical pathologies. Here we describe a case of mesenteric cystic lymphangioma mimicking an ileo-colic intussusception.